Detection of Staphylococcus aureus (MRSA/MSSA) in surfaces of dental medicine equipment - Gonçalves, Eva (Saudi J Biol Sci, 2020)
Methicillin-Resistant Staphylococcus aureus (MRSA) represents one of the major causes of nosocomial infections, leading to high mortality. Surfaces in clinics, as well as the attending uniform and the hands of the dental doctor can be MRSA reservoirs. Having this in mind, the purpose of this study was to evaluate the presence of Methicillin-Sensitive Staphylococcus aureus (MSSA) and MRSA on dental medicine equipment surfaces. 354 Samples were collected from six equipment surfaces in six attendance areas before and after patient consultation and cultured in a selective medium. Polymerase Chain Reaction (PCR) was used to confirm the identity of bacterial strains as MRSA or MSSA. Data analysis was performed with chi-square tests with Bonferroni correction. It was observed 55.6% of uncontaminated samples. Contamination was: 17.5% MRSA (5.9% of samples collected before patient attendance and 11.6% after); 39.3% MSSA (14.1% collected before and 25.2% after). The prevalence of MRSA and MSSA was significantly higher after patient care. Integrated Clinic represented the most contaminated attendance area (MRSA − 41.7%, MSSA − 51.2%), the chair arm rest was the most contaminated surface for MRSA (29.7%) and the dental spittoon the most contaminated surface for MSSA (23.5%). Although a low level of contamination was observed, dental clinics, through patients possibly carrying bacteria, may be reservoirs for MRSA and MSSA transmission, and might contribute to potential nosocomial infections.